Pulmonary cytotoxicity induced by bleomycin and methotrexate - Zh, V, Sheykh; A. O. Krutskevich; N. S. Drebushevskiy; S. N. Shvayko; A. P. Dunaev; V. G. Alekseev (Вестник рентгенологии и радиологии, 2016)
Early detection of drug-induced pulmonary parenchymal injuries is often hampered by nonspecific clinical and X-ray manifestations. The diagnosis is usually based on a history of drug use, clinical and X-ray presentation, and exclusion of other causes of lung tissue injury.Chemical preparations most commonly cause pathological pulmonary changes. Overall, about 10% of all patients receiving chemotherapy develop pathological changes in the lung parenchyma. The main chemical preparations causing lung injury are bleomycin, methotrexate, carmustine, busulfan, and cyclophosphamide.Out of all examination techniques, computed tomography is most sensitive in determining the presence, specific features, and trends in the development of drug-induced pulmonary parenchymaldisease.The paper gives the data available in the literature and 2 clinical observations of  pulmonary parenchymal disease induced by bleomycin and methotrexate.